2009
DOI: 10.1016/j.biochi.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-induced Akt phosphorylation regulates Bax activation

Abstract: Reactive oxygen species such as hydrogen peroxide (H 2 O 2 ) are involved in many cellular processes that positively and negatively regulate cell fate. H 2 O 2 , acting as an intracellular messenger, activates phosphatidylinositol-3 kinase (PI3K) and its downstream target Akt, and promotes cell survival. The aim of the current study was to understand the mechanism by which PI3K/Akt signaling promotes survival in SH-SY5Y neuroblastoma cells. We demonstrate that PI3K/Akt mediates phosphorylation of the pro-apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 80 publications
6
51
0
1
Order By: Relevance
“…Thus, it would appear that mitochondrial H 2 O 2 plays a role in reinforcing signaling programs in differentiating adipocytes. Hydrogen peroxide has also been found to induce the phosphorylation and activation of Akt and the autophosphorylation of insulin receptor, both of which play a part in the induction of adipocyte differentiation ( Papaconstantinou, 2009;Sadidi et al, 2009). Thus, it is possible that mitochondrial H 2 O 2 release serves as a positive feedback signal that prolongs the induction of adipocyte differentiation cascades.…”
Section: Adipocyte Differentiationmentioning
confidence: 99%
“…Thus, it would appear that mitochondrial H 2 O 2 plays a role in reinforcing signaling programs in differentiating adipocytes. Hydrogen peroxide has also been found to induce the phosphorylation and activation of Akt and the autophosphorylation of insulin receptor, both of which play a part in the induction of adipocyte differentiation ( Papaconstantinou, 2009;Sadidi et al, 2009). Thus, it is possible that mitochondrial H 2 O 2 release serves as a positive feedback signal that prolongs the induction of adipocyte differentiation cascades.…”
Section: Adipocyte Differentiationmentioning
confidence: 99%
“…4 B and C). Increased Bax/Bcl-2 ratio can lead to the release of cytochrome c and contribute to high cell apoptosis rate via caspase activation in the mitochondrial pathway [27,28]. Our data clearly suggested that Anxa11 knockdown might reduce Hca-F cell apoptosis through extrinsic apoptosis pathway.…”
Section: Anxa11 Knockdown Reduces Cell Apoptosis and Increases Bax/bcmentioning
confidence: 58%
“…The pro-survival function of Akt/protein kinase B depends on its phosphorylation of a number of downstream targets to inhibit cell death. Multiple pro-apoptosis proteins, including Bad [42], Bax [43], caspase-9 [44], glycogen synthase kinase-3-β (GSK-3β) [45], and forkhead transcription factors [46], are also phosphorylated by Akt. Akt not only phosphorylates these pro-apoptotic proteins, but also inactivates them, and retains them in the cytoplasm to inhibit the transcription of relevant pro-apoptotic genes, thereby suppressing cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%